Ancient Tsunami Records in the Viscous Remanent Magnetization of Reworked Boulders in the Kingdom of Tonga - Tetsuro Sato; Norihiro Nakamura; Masahiko Sato; Chie Kato; Kazuhisa Goto; Masashi Watanabe; Kenji Satake; Taaniela Kula (Geophysical Research Letters)
Abstract The movement history of boulders is crucial for the reconstruction of paleo‐tsunamis. We report findings from viscous remanent magnetization studies of the boulders on Tongatapu Island, aiming to reconstruct their reworkings. Two boulders exhibited viscous remanence, whereas two larger boulders lacked viscous components but exhibited stable remanence. Both the viscous and stable components deviated from the geomagnetic field direction. These observations indicate that: (a) the boulders with a viscous component were reworked before the latest event, which could have reworked all boulders, and (b) the magnitude of the latest event was larger than that of an earlier event. The reworked timing indicated that the event occurred between 3,000 years ago and the fifteenth century. The difference in the wave height required to move boulders on the eastern and western coasts suggests that the source of the earlier tsunami was likely an eruption due to volcanoes along the Tonga Ridge.